The missing ethical dimension: an application of TCE to the case of the Inquiry Committee into Oil-for-Food Program Scandal - Da Veiga, M. R. (European Accounting Association Congress, 2016)
This paper demonstrates that Transaction Cost Economics (TCE) alignment hypothesis did not verify and “probity” hazards – “ethics” – cannot be relieved by governance structures, i.e., incentives, in the case of the inquiry into the Oil-For-Food Programme (OFFP) scandal at the United Nations (UN). The inquiry, which contains “sovereign” as well as “quasi-judiciary” transactions’ elements, and though lack the “authority of the sovereign” and the “independence of the judiciary” attributes, did not achieve its stated purposes. We apply Williamson’s TCE theory (1999) and McCloskey’s (2006) “virtues ethics” to the questions: i) has the inquiry worked? ii) has TCE’s discriminating alignment hypothesis been verified in the case of the OFFP scandal inquiry? The longitudinal historical narrative analytical case based research covering more than 20 years of history was developed to address decisions of oversight governance structures at the UN in the context of systemic failures of probity / ethics. The UN took adaptive ex post action and reformed internal oversight governance structures in a movement that might have been devised mainly to help rebuild reputation and secure funding continuation but which intrinsically changed little. We argue that TCE should be modified to include McCloskey’s “virtues ethics” behavioral dimension as a transaction costs’ reduction device and an explanatory framework for bureaucratic ethical failures.